Socioeconomic disparities in access to a hepatocellular carcinoma screening program in Brazil (Clinics, 2016)
OBJECTIVES: Cirrhotic patients must receive an abdominal ultrasound every 6 months as part of hepatocellular carcinoma (HCC) screening. The aim of this study was to assess if HCC screening was performed as recommended by the literature and to observe the differences between the private and public services in Brazil. METHODS: We analyzed data from the HCC screenings of 253 cirrhotic patients from the University Hospital (n=177) and private sector (n=76) in Vitória, ES, Brazil. RESULTS: Ultrasound screening was performed every 13.1 months on average (SD 9.02). In 37 out of 253 patients, the screenings were performed close to the recommended frequency; 16 were performed every 6 months, and 21 were mostly performed during the follow-up period every 6 months. In the remaining 216 cases, ultrasounds were not performed according to the guidelines; for 106 patients, less than 50% of all ultrasounds were performed every 6 months and 110 patients showed an interval greater than one year. Patients from the private sector received ultrasound screenings near the ideal in 28.9% of cases, while patients from the University Hospital received ultrasounds in only 8.4% of cases (p